Measuring the Gap : Female Education in Sub-Saharan Africa - Hartnett, Teresa (World Bank, Washington, DC, 2012)
Given the significance of female education for development, there is an enormous need for data across countries that can be used to inform policy discussions within and among individual countries. Nowhere, perhaps is this need greater than in sub - Saharan Africa (SSA) where female participation in education is inordinately low, and where disparities between females and males vary greatly among countries. the report previewed in this article responds in two ways to the need for statistics on female education. First, it defines statistical indicators that can be used to describe the level of female participation and the disparities between males and females in education systems. As one form for these indicators, the report introduces the concept of the gender ratio as a generic tool for comparing male and female participation in education across all indicators used to assess the performance of education systems. Second, the report presents data from existing sources for the forty-six countries in sub - Saharan Africa.